1985
DOI: 10.5636/jgg.37.509
|View full text |Cite
|
Sign up to set email alerts
|

The D-region winter anomaly and dynamical effects of atmospheric planetary-scale waves.

Abstract: A study is presented of the D-region winter anomaly, observed by ground based measurements of long-distance VLF radio wave propagation and HF radio wave vertical sounding at several stations located in and near Japan over 3 winters from 1974 to 1977. These winters have different meteorological conditions (i.e., a major stratospheric sudden warming in the winter 1976/77, a minor warming in 1974/75 and no warmings in 1975/76). The activity of the anomaly is compared with that of planetary-scale waves using atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…He concluded that the D-region electron density at 75-90 km is enhanced during SSW events, resulting in a notable lowering of the VLF nighttime reflection height. Subsequent studies [e.g., Muraoka, 1985;Muraoka et al, 1986] strengthened these findings, while noting that the winter anomaly occurrence is associated with a mesospheric planetary wave with zonal wave number 1.…”
Section: The 'Winter Anomaly' and Long-term Meteorological Effectsmentioning
confidence: 95%
“…He concluded that the D-region electron density at 75-90 km is enhanced during SSW events, resulting in a notable lowering of the VLF nighttime reflection height. Subsequent studies [e.g., Muraoka, 1985;Muraoka et al, 1986] strengthened these findings, while noting that the winter anomaly occurrence is associated with a mesospheric planetary wave with zonal wave number 1.…”
Section: The 'Winter Anomaly' and Long-term Meteorological Effectsmentioning
confidence: 95%